1969
DOI: 10.1113/jphysiol.1969.sp008910
|View full text |Cite
|
Sign up to set email alerts
|

Radial spread of contraction in frog muscle fibres

Abstract: SUMMARY1. The membrane potential of isolated muscle fibres in solutions containing tetrodotoxin (TTX) was controlled with a two-electrode voltage clamp. The striation pattern in the region of the electrodes was observed microscopically.2. With square steps of depolarization of increasing magnitude, contraction occurs first in the myofibrils just beneath the surface membrane, and then spreads inwards towards the axis ofthe fibre asthe depolarization is increased.3. From the depolarizations which make the superf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
1

Year Published

1970
1970
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(128 citation statements)
references
References 17 publications
6
121
1
Order By: Relevance
“…Adrian, Costantin & Peachey (1969) Fig. 4A show that the larger the depolarization, the shorter the time to reach peak current.…”
Section: Resultsmentioning
confidence: 99%
“…Adrian, Costantin & Peachey (1969) Fig. 4A show that the larger the depolarization, the shorter the time to reach peak current.…”
Section: Resultsmentioning
confidence: 99%
“…There are a number of theoretical papers which claim, however, that circumferential and radial potential gradients should exist and be significant in cylindrical muscle fibers (Eisenberg and Johnson, 1970;Barcilon et al, 1971;Peskoff et al, 1972; a review of the literature can be found in Peskoff and Eisenberg, 1973). There are some indirect indications of circumferential and radial potential gradients in the experiments of Adrian, Costantin, and Peachey (1969) and Costantin (1970) but there has been no direct experimental evidence concerning the existence of these effects, let alone their quantitative significance, and so we thought it worthwhile to seek such evidence. Impedance measurements were made by the techniques described by Valdiosera et al, 1974 a. Measurements were made at two different circumferential positions of the voltage microelectrode, the longitudinal position being constant, and the radial position being unknown.…”
Section: Circumferential Variation Of Potential Experimental Evidencementioning
confidence: 99%
“…The original analyses of the local potential (Weinberg, 1942;Falk and Fatt, 1964;Eisenberg, 1967;Adrian, Costantin, and Peachey, 1969) seem somewhat complex and not amenable to physical interpretation, but the approximate treatment of Eisenberg and Johnson, 1970, reduced the complexity of the pi oblem. Recent results using singular perturbation theory provide a simple physical interpretation of the local potential and its interaction with the potential given by the usual expressions of one-dimensional cable theory.…”
Section: Circumferential Variation Of Potential: Theoretical Modelmentioning
confidence: 99%
“…Radial gradients are possible only with circuits in which some resistance or capacitance must be spatially distributed through the fiber cross-section. Consequently, assuming the contractile system to be uniform across the fiber, only circuits of the latter type can account for the findings that deep myofibrils are activated later (Gonzalez-Serratos, 1966) and require a larger surface membrane depolarization for activation (Adrian, Costantin, and Peachey, 1969) than those near the fiber surface. The results of the present paper indicate that a closer approximation to fiber input impedance can be obtained using a circuit having some spatially distributed elements than can be obtained using circuits having only lumped impedance elements.…”
mentioning
confidence: 99%